(untitled) (Al-Qamar, 2019)
The word “Usool” is the plural of the word “Asl" which means the base or root of something. Every area of study or knowledge has some basic maxims which help to explore and understand that area of study, whereas the literal meaning of the word Tafsīr is to describe and explain things clearly. In terms of connotative meaning, Tafsīr is that are of study which describes the meanings of Quranic terms, its implications and the logics behind particular rules of Quran. Imām Ibn-e-Taimia says: “Usool are the collection of those rules which must be considered by Mufassireen to interpret the words of Quran and to derive logics and wisdom from the verses of Quran” The objectives of the Ilm-e-Tafsīr is to describe the meanings of the words of Quran , explanations of the verses of Quran and the Tafsīr of the meanings of the Quranic verses so that to get benefits from Quran in this world and world hereafter. In the era of prophet Mohammad (SAW), his companions used to understand the meanings of Quran directly by prophet Mohammad (SAW), so there were 10 famous Mufassireen in the age of prophet Mohammad (SAW) excluding four caliphs. They are the following: Hazrat Abdullah Ibn Masood, Hazrat Abdullah Ibn Abbas, Hazrat Ubaee Ibn Ka‘b, Hazrat Zaid Ibn Thābit, Hazrat Abū Mousa Ash̒arī and Hazrat Abdullah Ibn Zuabir . In the age of prophet Mohammad (SAW) there were four derivatives of Tfseer-e-Quran: 1. Quran Hakeem 2. Ahaadith3.Ijtehad and Sayings of Shahba.4. Ahl-e-Kitāb. In this topic Usool-e-Tafseer, its history and its evolution will be discussed.